RANCANGAN APLIKASI SISTEM UJIAN RATING TEORI BERBASIS WEBSITE BAGI PERSONEL AERONAUTICAL COMMUNICATION OFFICER DI PERUM LPPNPI CABANG PONTIANAK - Ni Putu Santika Enno Purwanti; Dewi Ratnasari; Siska Wijayanti (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Perum LPPNPI Pontianak Branch is one of the airports that provides air navigation services in West Kalimantan. Aeronautical communication personnel are required to conduct a rating test once a year so that the license remains active or valid. Based on the PM 1 of 2014 document concerning Civil Aviation Safety Regulation Part 69 (Civil Aviation Safety Regulation Part 69) concerning License, Rating, Training and Skills of Aviation Navigation Personnel, aeronautical communication personnel are required to take a rating test to test the license. Therefore, a web-based rating test is needed to be more effective for participants and checkers. The application of the website-based theory rating test in the application includes registration for rating exams, online file submission, material refreshing, working on multiple-choice and true or false questions which include pictures and videos, automatic correction for multiple choice. This study uses a waterfall research methodology. The result of the research is that the web-based rating test has been implemented and received a positive response from each examinee. It is hoped that in the future the Management at Perum LPPNPI Pontianak Branch can consistently apply the website-based theory rating test.